LITHIUM IN AMPHIBOLES: DETECTION, QUANTIFICATION, AND INCORPORATION MECHANISMS IN THE COMPOSITIONAL SPACE BRIDGING SODIC AND BLI-AMPHIBOLES - Oberti R.; Cámara F.; Ottolini L.; Caballero J.M. (My University, 2003)
Lithium is an important constituent in amphiboles, where it can be incorporated up to a limit of three atoms per formula unit (apfu). Lithium can partition itself between the B-group sites (where it occurs at the [6+2] -coordinated M4' position) and the C-group sites (where it occurs at the M3 site). Systematic analysis of the available chemical (EMP + SIMS) and structural data constrains lithium occurrence in amphiboles to the following compositions and exchange vectors: (1) BLi is incorporated according to (M4)'Li Na-M4(-1), and no miscibility gap is apparent, despite the difference in the ionic radii; (2) Li-C is incorporated according to Li-M3 Fe-M2(3+) Fe-M3(-1)2+ Fe-M2(-1)2+; however, a partial bond-strength contribution is provided by Si at the T1 site and by Na or K at the Am site. Amphiboles with Li-C > 0.5 apfu (root names: leakeite, kornite, whittakerite and pedrizite) have more than half-occupied A-group sites. Seven new amphibole end-members containing lithium have been discovered in epysienites (dequartzified and albitised granites) from the Pedriza Massif (Central Spain), where lithium incorporation and partitioning is controlled both by the composition of the fluid and the temperature conditions of crystallisation. This occurrence provides an unique opportunity to characterise the (M4)'Li double left right arrow Na-M4 and Li-M3 double left right arrow Fe-M3(2+) solid solutions, as well as model crystal-chemical mechanisms and understand, their dependence on intensive parameters. An accurate quantification and partitioning of lithium in amphiboles is not trivial, and requires a combination of ion-microprobe analysis and structure refinement. Analysis of the available data provides criteria for calculating reliable H2O and Li2O values, as well as for obtaining reliable unit formulae from routine EMP results. These criteria can then be used to simplify petrological studies in Li-rich environments.
Keywords: Amphiboles